Development of ECG and Temperature Sensors for Infant Incubator - Noorizan, Farah Najidah; Jumadi, Nur Anida (Evolution in Electrical and Electronic Engineering, 2024)
Infant incubators help doctors monitor all the different aspects of the child’s environment and used to create conditions that were similar to those that were in the ideal conditions inside the mother’s womb, preserving the life of premature babies and reducing infant baby death. This work aimed is to develop an IoT infant incubator with ECG and temperature sensors. This development of infant incubator utilizes the microcontroller Arduino Durian Uno as the primary CPU along with DS18B20 temperature sensor and AD8232 ECG sensor. With the advancement of Internet of Things (IoT) technology, this interface can be viewed through the Blynk application in the user’s tablet, allowing for continously monitoring. The device has been developed successfully, and both sensors are operational. Four healthy people were invited to participate in the ECG reading measurement and the recorded BPM is between 108 and 144. However, the ECG sensors has a low accuracy, with the percentage error around 32% to 55%. On the other hand, the temperature sensor has a low variance value between 0.02 and 0.49 indicating that the sensor is very accurate.